2006
DOI: 10.1002/adem.200600013
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐Scale Design of TiAl Alloys Based on β‐Phase Decomposition

Abstract: Phase decomposition and ordering reactions in β/B2‐phase containing TiAl alloys were utilized to establish a novel, previously unreported, type of laminate microstructure. The characteristic constituent of this microstructure are laths with a nanometer‐scale substructure that are comprised of several stable and metastable phases. Microstructural control can be achieved by conventional thermomechanical processing and leads to a structurally and chemically very homogeneous material with excellent mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 18 publications
4
79
0
3
Order By: Relevance
“…Alloying and heat treatments are effective ways to overcome the brittleness and to improve the hot workability. The usage of these techniques can lead to the formations of several lower symmetry ordered phases in the microstructure [1][2][3]. Among lower symmetry phases, the orthorhombic B19 phase is commonly observed in γ-TiAl-based intermetallics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alloying and heat treatments are effective ways to overcome the brittleness and to improve the hot workability. The usage of these techniques can lead to the formations of several lower symmetry ordered phases in the microstructure [1][2][3]. Among lower symmetry phases, the orthorhombic B19 phase is commonly observed in γ-TiAl-based intermetallics.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated G/B ratios of B19 TiAl from the EDM is 10.03% and 14.18% lower than the theoretical data of γ-TiAl (0.62) and α 2 -Ti 3 Al (0.65) [42], respectively, indicating that B19 TiAl is more ductile than γ-TiAl and α 2 -Ti 3 Al. Experimentally, Appel et al [3,[8][9][10] have measured the mechanical properties of γ-TiAl-based intermetallics with the microstructure containing B19 phase and found that the existence of B19 structure can give the intermetallics relatively high tensile ductility. According to Pettifor's rule [12], a material has more metallic (angular) bonds and thus is more ductile (brittle) if it has a larger positive (negative) Cauchy pressure.…”
Section: Elastic and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these are hexagonal ω-related phases [9] and orthorhombic phases. [10,11] Abe et al [10] reported on an orthorhombic phase with B19 structure (Pmma) that forms very fine precipitates upon rapid cooling in a Ti-48 Al alloy. Tanimura et al [12] observed the formation of B19-phase as a metastable transitional phase during the A3→D0 19 +L1 0 precipitation sequence.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to improve their ductility and hot workability is to employ a combination of alloying and heat treatments to encourage the formation of more ductile phases. Nevertheless, the strategy can also induce the formations of some lower symmetry ordered phases which are constituents of the microstructure [1][2][3]. As a significant constituent, the orthorhombic B19-TiAl phase is commonly observed in TiAl-based alloys [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%